Priority questions for biodiversity conservation in the Mediterranean biome: Heterogeneous perspectives across continents and stakeholders - Francisco Moreira; Nicky Allsopp; Karen J. Esler; Grant Wardell‐Johnson; Leonardo Ancillotto; Margarita Arianoutsou; Jeffrey Clary; Lluis Brotons; Miguel Clavero; Panayiotis G. Dimitrakopoulos; Raquel Fagoaga; Peggy Fiedler; et al. (Conservation Science and Practice, 2019)
Abstract The identification of research questions with high relevance for biodiversity conservation is an important step towards designing more effective policies and management actions, and to better allocate funding among alternative conservation options. However, the identification of priority questions may be influenced by regional differences in biodiversity threats and social contexts, and to variations in the perceptions and interests of different stakeholders. Here we describe the results of a prioritization exercise involving six types of stakeholders from the Mediterranean biome, which includes several biodiversity hotspots spread across five regions of the planet (Europe, Africa, North and South America, and Australia). We found great heterogeneity across regions and stakeholder types in the priority topics identified and disagreement among the priorities of research scientists and other stakeholders. However, governance, climate change, and public participation issues were key topics in most regions. We conclude that the identification of research priorities should be targeted in a way that integrates the spectrum of stakeholder interests, potential funding sources and regional needs, and that further development of interdisciplinary studies is required. The key questions identified here provide a basis to identify priorities for research funding aligned with biodiversity conservation needs in this biome.